Penerapan Analisis Logo dalam Perusahaan Batik Pesisir, Thamrin City - Muhammad Ramdhany Sisna; Satya Yudha Azwir (MES Bogor, 2024)
The purpose of this research is to provide information, present data, and promote businesses to the community in the Thamrin city area, Central Jakarta, and design a business identity to make the brand easily recognizable and distinguish it from competitors in a crowded market, as well as help the business develop. in accordance with the determined target market. The research method was carried out through various stages, namely data collection through websites, reference books, and interviews with the owner as the business owner. What this research aims to achieve is a promotional video and brand visual identity that is packaged with the aim of presenting a new approach that is unique and attractive to readers. The results of the video design show the journey of business development and can make this business known to the wider community.